Pondering Deeper, Ahead and Beyond Over the Use of ChatGPT in H(A)Igher Education - Soroliou, Elena; Kritikou, Maria Ontil; Antonopoulos, Sotiris; Kania, Anna (HAPSc Policy Briefs Series, 2023)
While within the last months several studies reveal the real and full implementations of the cutting edge ChatGPT in higher education institutions, a comprehensive examination of its potential at the micro and macro levels of higher education is crucial. To address this gap, this policy brief scrutinises the integrated and potential capabilities of ChatGPT through three lenses-levels: student-facing, teacher-facing, and system-facing advantages, disadvantages, blind spots, challenges, and risks. The core aim of this policy brief is to research and shed light on a robust and nuanced understanding of the level of (in-)appropriateness of ChatGPT’s use in higher education among core stakeholders, i.e. educators, students, and administrators, who co-sign an “educational contract” via core emerging trends and implications. Finally, a set of applicable recommendations is presented for policy makers, other interlocutors, and future researchers, in order to walk the talk for a more ethical, inclusive and equitable use of AI in higher education, since a “one-size fits all” approach should be strongly avoided.